Cancellation of Deed of Sale and Purchase of Land Rights Due to Unlawful Actions - Ariatami Edwina, Yossica; Anggriani, Reni (Journal of Private and Commercial Law, 2023)
The deed of sale and purchase agreement (APJB) is a preliminary agreement prior to the transfer of land rights in PPAT which regulates the rights and obligations of the parties and is made based on Article 1320 of the Civil Code concerning the legal terms of the agreement and Article 1338 of the Civil Code concerning the principle of freedom of contract and the principle of good faith by not contrary to law,  order and decency, but in certain conditions the sale and purchase binding agreement can be found to have been canceled by one of the parties to the court because of an unlawful act such as a civil case in East Jakarta District Court decision No. 267/Pdt.G/2019/PN Jkt. Tim. This study analyzes the basis for the judge's consideration in canceling the APJB land rights and the legal consequences of canceling the deed. This type of legal research is normative juridical, namely examining the literature on regulations and literature related to the object of the problem. The results of this study are the basis for the judge's consideration in canceling the APJB of land rights, namely the binding sale and purchase agreement between the seller (plaintiff) and the buyer (defendant) without or not based on an extraordinary power of attorney to sell or carry out binding sales and purchases so that the issuance of the deed is legally flawed. The legal consequences arising from the cancellation of the APJB land rights are null and void and do not have the force of law to bind the parties anymore.Keywords: Sale and Purchase Binding Deed, Cancellation, Unlawful Act.